Idrijsko hribovje kot primer demografsko ogroženega območja - Benkovič Krašovec, Monika (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The article analyses two criteria: rate of growth of population and ageing index, which in Slovenia define demographically endangered areas. There are also mentioned some causes and consequences of unfavourable demographic trends in Idrijsko hribovje region.
Keywords: agrarna geografija; demografski razvoj; depopulacija; Idrijsko; podeželje; poselitev; rural area; Slovenia; Slovenija